2015
DOI: 10.1002/app.41969
|View full text |Cite
|
Sign up to set email alerts
|

Structural, rheological, and mechanical properties of PA6/SAN/SEBS ternary blend/organoclay nanocomposites

Abstract: The aim of this study was to investigate the effect of nanoclay addition on the morphological and mechanical properties of PA6/SAN/SEBS ternary blend. Two different nanoclays with different modifiers and two different mixing sequences were used to investigate the role of thermodynamic and kinetic, respectively, in the nanoclays localization. XRD, SEM, TEM, melt rheology, tensile and Izod impact tests were used to characterize the nanocomposites. Results of characterization of nanocomposites showed that clay lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 36 publications
(61 reference statements)
3
22
0
Order By: Relevance
“…It is due to the kinetic effect of this protocol (initially mixing of EVOH and Cloisite 15A). A similar finding was reported for the PA6/SAN/SEBS/organoclay nanocomposites …”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…It is due to the kinetic effect of this protocol (initially mixing of EVOH and Cloisite 15A). A similar finding was reported for the PA6/SAN/SEBS/organoclay nanocomposites …”
Section: Resultssupporting
confidence: 89%
“…In fact, polar groups of PA‐6 chains can create chemical and physical interactions with hydroxyl groups of the organic modifier (MT2ETOH) in Cloisite 30B, and as a result, melt intercalation takes place efficiently in the PA‐6/nanoclay masterbatch. Similar observations regarding affinity of the PA‐6 matrix to different organoclays especially Cloisite 30B have been reported by Kelnar et al, Filippone et al, Zanjanijam et al, and Babaei et al…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Incorporation of nanoparticles into the polymer blends has been the subject of a great number of researches in academia and industry. This approach is associated with interesting results such as improving the mechanical properties, adding new characteristics, such as electrical properties, or controlling of the phase morphology . For example, Elias et al reported that silica nanoparticles induced a decrease in the effective interfacial tension between polypropylene (PP) and ethylene vinyl acetate phases and thereby a lower particle size for dispersed phase .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the homogeneous dispersion of nanoparticles in polymer matrix significantly improves the properties of nanocomposites . However, good dispersion of inorganic particles in organic polymer matrix becomes difficult when the dimension of particles approached nanoscale . It results in aggregation/agglomeration of nanoparticles in polymer matrix due to lack of compatibility between nanofiller and polymer matrix.…”
Section: Introductionmentioning
confidence: 99%